A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae) - Hou, Xiao-Jiao; Zhang, Ya-Lin; Huang, Min (Zootaxa, 2016)
The genus Guheswaria Thapa is recorded for the first time from China; two new species, Thampoa quinquemaculata sp. nov. and Guheswaria brevicula sp. nov. are described; one species, Guheswaria linguplata rec. nov. is newly recorded from China; and one new combination, Thampoa alata (Dworakowska, 1994) comb. nov. (from Guheswaria) is proposed. A checklist and updated keys to species of Thampoa and Guheswaria are provided.